“If It Feels Right, Do It”: Intuitive Decision Making in a Sample of High-Level Sport Coaches - Collins, Dave; Collins, Loel; Carson, Howie J. (Frontiers in Psychology, 2016)
Comprehensive understanding and application of decision making is important for the professional practice and status of sports coaches. Accordingly, building on a strong work base exploring the use of professional judgement and decision making in sport, we report a preliminary investigation into uses of intuition by high-level coaches. Two contrasting groups of high-level coaches from adventure sports (n = 10) and rugby union (n = 8), were interviewed on their experiences of using intuitive and deliberative decision making styles, the source of these skills, and the interaction between the two. Participants reported similarly high levels of usage to other professions. Interaction between the two styles was apparent to varying degrees, while the role of experience was seen as an important precursor to greater intuitive practice and employment. Initially intuitive then deliberate decision making was a particular feature, offering participants an immediate check on the accuracy and validity of the decision. Integration of these data with the extant literature and implications for practice are discussed.